DESIGN AND CONTROL OF A MULTI-LEGGED ROBOT WITH GEAR ROD COMBINATION MECNANISM - WANG XiangLing; ZHANG Lin (Jixie qiangdu)
Based on crawling patterns of arthropod such as spiders and crabs,a multi-legged robot with gear rod combination mechanism was designed by drawing method which met the requirements of predetermined trajectory. Solid Works software was used to assemble the robot parts. Motion module was used to make kinematics simulation analysis by adding a motor,and the velocity curve of claw-end was obtained,which verified the feasibility of the mechanism. In addition,the robot carried the TGAM EEG module to collect EEG（ Electro Encephalo Gram） data,and then sent it to PC through bluetooth serial port,and finally sent the data to Arduino platform to control the multi-legged robots to go forward at different speeds,so as to achieve the realization of brain wave control robot.